![B)y=2(x-2)^2+4](https://img.qammunity.org/2023/formulas/mathematics/college/be4f1u9h7p5h5bkpu0oh0fxmd7hj85523v.png)
1) Since the vertex is at (2,4) and there is another point, we can write out the following using the vertex quadratic form and those points:
![\begin{gathered} y=a(x-h)^2+k \\ \\ 6=a(3-2)^2+4 \\ \\ 6=a+4 \\ \\ 6-4=a \\ a=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kzuwd6i253fg4jl9lf5j6mrjqe72pc5rv4.png)
2) Now, that we know the coefficient "a" we can tell that this is the equation of that parabola by plugging a=2 into the vertex form:
![y=2(x-2)^2+4](https://img.qammunity.org/2023/formulas/mathematics/college/3g1g46n565nrposgv78gfs4wojbkodtrdj.png)
And that is the answer.